The analysis of face theory based on the five basic emotions from the movie Inside Out - Nur Aiman Fatihah Mazhan Rizal,; Normalis Amzah, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Humans interact by sensing each other’s face expressions to build social relationships. The way people respond to each other indicates reverence and respect, and this is considered as a sign of approval. This study focuses on Face Theory proposed by Brown and Levinson (1987) which centers around how people want their objectives, possessions, and accomplishments to be regarded as desirable by someone notably significant to a specific objective. The movie Inside Out was chosen for the study because it the theme of the movie is materializing human’s emotion by illustrating the face and emotions of human beings. This study aims to identify the positive and negative faces based on the five basic emotions (Joy, Sadness, Fear, Anger and Disgust) shown by the main character from the movie. This study is designed as qualitative research. The data is taken by watching the movie and transcript relevant script. The findings show that the main character performs positive face under the influence of emotion Joy and negative face under the influence of Anger and Sadness in accordance to the situations. The findings allude those negative emotions are needed equally as much as positive emotions to properly express oneself. Although human’s face and emotions can be masked, it is necessary to be expressed instead of being suppressed only.